Aiming for Tomorrow: Breakthrough Strategies in Public Sector Talent Management - Fauzian, Nurhakim Ramdani; Prasojo, Eko; Muslim, Muhammad Azis; Wangsaatmaja, Setiawan (Jurnal Borneo Administrator, 2024)
The West Java Provincial Government is adopting technology-driven talent management. This empirical study explores digital-based civil service talent management, emphasizing its role in supporting merit-based placement. Key steps involve digital models, employee profiling, talent mapping, and leveraging information systems. This digital approach yields comprehensive, measurable talent data and transforms HR management into a more objective and efficient process. Successful implementation depends on leadership commitment, HR capabilities, and robust IT infrastructure. Future research could explore the impact of these processes on individual and organizational performance. Policy recommendations for the West Java Province include enhancing leadership commitment to digital transformation in talent management, developing HR manager skills in digital systems and evidence-based decision-making, investing in IT infrastructure, integrating and standardizing talent management systems, and formulating sustainable policies for digital talent management development, including data privacy and security